تیسیر المرام لأدعیة خیر الکلام : کشاف موضوعى هجائى للأدعیة الواردة فى القران الکریم - د. أحمد رجب شاهین Ragab Shaheen (المجلة الدولية لعلوم المكتبات والمعلومات)
This research is concerned with enumeration and recording of theinvocations in the Holy Quran, the determination of its topics and the formulationof its indexing entries. This is done in order to prepare an alphabetical subjectindex for invocations in Holy Ouran, So that the index in the end is a tool tofacilitate the use and access to these invocations on the hand, and an objectivecollection on the other hand.the study Problem:The problem of the study is concentrated in two aspects:1- The difficulty of reaching a specific invocation in certain subject ofinvocations in the Holy Quran. This is because the works that are concernedwith the Quranic invocations order are arranged according to the order of thesurah in the Mus-haf. This arrangement is unuseful to achieve easy and fastaccess to an invocation on a specific subject.2- The existence of the so-called wrongdoing in invocation, which is to ask Allahwhat is not appropriate and it is not permissible to ask for it, such as helpingto commit sin, looking at the unseen, or invocation on oneself and relativeswith destruction and evil ... and others that contradict the wisdom of Allahand his law.Objectives of the study :The researcher aims to achieve the following :1- Compilation of the invocations mentioned in the Holy Quran, in order toguide the Muslims to it.2- Facilitating access to the invocations in the Holy Quran according to itstopics.3- The preparation of an alphabetical subject index as a goal in itself, as wellas being a means to achieve the two previous goals, in which theinvocations will be organized under indexing entries(subject headings)which represent it .